Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Donat Madu Pada Donat Madu Cihanjuang Cabang Rangkasbitung - Mia Antika; Aldila Rahma Putri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine the effect of price and product quality on purchasing decisions for Honey Donuts at Honey Donuts Cihanjuang Rangkasbitung Branch. The method used is the associative descriptive method. The sampling technique used is simple random sampling with sampling using the Slovin formula and obtained 91 respondents. Data analysis using validity tests, reliability tests, classical assumption tests, regression analysis, determination coefficient analysis and hypothesis testing. The results of the analysis found that price (X1), product quality (X2) have a positive effect on purchasing decisions (Y) and are significant. With the regression equation Y = 6,244 + 0.403 X1 + 0.352 X2. The correlation value of 0.828 is in the interval 0.80-1,000 (very strong). The determination coefficient value is 68.5% while the remaining 31.5% is influenced by other factors. The hypothesis test obtained the Fcount value> Ftable or (95.774 > 3.95) and significant 0.000 < 0.005. Thus Ho is rejected and H3 is accepted. This means that there is a significant influence simultaneously between Price and Product Quality which have a significant effect on Purchasing Decisions at Cihanjuang Rangkasbitung Honey Donuts.